Diurnal Variations of Total Electron Content over Equatorial Ionosphere: Ile-Ife South Western Nigeria - Fayose, Sola; Okoye, Peter Chibuike (European Journal of Applied Sciences, 2021)
The studies of equatorial ionosphere were carried out using data collected from Global Positioning System Scintillation Network and Decision Aid (GPS-SCINDA) facility at Ile-Ife, Nigeria (7.4667 N, 4.5667 E). The ionospheric parameters were computed every 60 seconds for a period of one month. The daily variabilities of Total Electron Content (TEC) values for the ionospheric experimental campaign were used for the computations and analysis. The daily maximum TEC values occur in the afternoon period, largely due to the large amount of solar radiation entering the ionosphere during while minimum TEC values were observed in the morning and evening periods. A maximum value of TEC for each day was around 30TECU to 40TECU. The greatest maximum TEC value was approximately 45TECU and it was observed at 13.00 hours and 17.00 hours respectively. The results obtained show a strong correlation between the solar radiation coming into an equatorial ionosphere and the variations in its Total Electron Content (TEC) values. The TEC values of equatorial ionosphere are sufficiently affected by the effects of solar activity.